The human Bosniak model applied to a cat with renal cystadenoma - Baloi, P.; Del Chicca, F.; Ruetten, M.; Gerber, B. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2015)
A 13-year-old domestic shorthair cat was presented with weight loss and azotemia. Abdominal ultrasound revealed a large cystic spaceoccupying lesion with multiple septae in the left kidney. A core needle biopsy yielded a renal cystadenoma originating from the epithelial cells. This report describes the clinical, ultrasonographic and computed tomographic features and the growth progression of a renal cystadenoma. We describe the first attempt to apply the human Bosniak classification to a cat with renal cystic neoplasia to differentiate between benign and malignant lesions. Cystadenoma should be a differential diagnosis in cases of renal cystic space-occupying lesions. Other differentials, imaging features to differentiate benign and malignant lesions and the risk of malignant transformation will be discussed.
Keywords: Renal cystic mass; cystadenoma; Bosniak classification; computed tomography; ultrasound; cat